2020
DOI: 10.1111/trf.15807
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a broad spectrum of viruses and parasites by photochemical treatment of plasma and platelets using amotosalen and ultraviolet A light

Abstract: BACKGROUND The INTERCEPT Blood System pathogen reduction technology (PRT), which uses amotosalen and ultraviolet A light treatment (amotosalen/UV‐PRT), inactivates pathogens in plasma and platelet components (PCs). This review summarizes data describing the inactivation efficacy of amotosalen/UVA‐PRT for a broad spectrum of viruses and parasites. METHODS Twenty‐five enveloped viruses, six nonenveloped viruses (NEVs), and four parasites species were evaluated for sensitivity to amotosalen/UVA‐PRT. Pathogens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 114 publications
(226 reference statements)
0
48
0
Order By: Relevance
“…There are evidences that SARS‐CoV‐2 might not be transfused by blood components 76 . However, pathogen reduction should not be neglected in case it is already available, particularly due to its capacity of coronavirus inactivation 77,78 . The possibility of having hundreds or thousands of donors participating in CCP programs (intended for older, immunosuppressed patients or patients with different comorbidities), harboring detectable RNA for many days after recovery (especially after the standard 28‐day temporary deferral period), some with no molecular tests as screening procedures and no PR methods applicable, should be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences that SARS‐CoV‐2 might not be transfused by blood components 76 . However, pathogen reduction should not be neglected in case it is already available, particularly due to its capacity of coronavirus inactivation 77,78 . The possibility of having hundreds or thousands of donors participating in CCP programs (intended for older, immunosuppressed patients or patients with different comorbidities), harboring detectable RNA for many days after recovery (especially after the standard 28‐day temporary deferral period), some with no molecular tests as screening procedures and no PR methods applicable, should be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
“…This report represents the first case of a confirmed STR associated with a pathogen-reduced PLT unit, although possible STRs have been reported. 4 Using the INTER-CEPT process, PR is also considered robust for a wide variety of viruses and parasites 22 ; however, breakthrough cases of hepatitis E virus, a known PR-resistant virus, have occurred. 23,24 Our investigation demonstrated that the INTERCEPT process was successfully performed and that >5.9-log/mL in vitro inactivation occurred for both ACBC and SS isolates provided by the hospital microbiology laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen inactivation technology poses an additional layer of safety to reduce the risk of pathogen transmission. AS pathogen inactivation, which we evaluated in our study, efficiently inactivates blood borne viruses and other pathogens of concern in human plasma, 13 also HIV, HBV and HCV (viruses which could be transmitted despite the usage of state of the art screening tests during a window period).…”
Section: Discussionmentioning
confidence: 99%
“…The key objectives for this production method are the prevention of transmission of infectious agents and the preservation of the haemostatic capacity as well as the clinical effectiveness. AS‐treatment of plasma effectively inactivates a broad spectrum of pathogens, including newly emerging pathogens 13,14 . In vitro studies revealed a moderate loss of coagulation factors post PI‐treatment, with an overall retention meeting the regulatory criteria for therapeutic use 15,16 .…”
Section: Introductionmentioning
confidence: 99%